Rice polish: An alternative to conventional adsorbents for treating arsenic bearing water by up-flow column method - Ranjan D.; Talat M.; Hasan S.H. (My University, 2025)
"Rice polish", an agrowaste from rice milling industries, was utilized as potential biosorbent for removal of arsenic from water in a continuous up-flow fixed bed column system. The experiments were conducted to study the effect of important design parameters such as bed height, flow rate, and initial metal ion concentration. At a bed height of 25 cm, flow rate 1.66 mL/min, and initial metal ion concentration 1000 μg/L, the metal uptake capacity of rice polish for As(III) and As(V) was found to be 66.95 and 78.95 μg/g, respectively. The bed depth service time (BDST) model was used to analyze the experimental data. The computed sorption capacity (No) was 28776 and 28248 μg/L for As(III) and As(V), respectively. The rate constant (Ka) was recorded as 0.117 × 10-3 and 0.26 × 10-4 (L/μg)/min for As(III) and As(V), respectively. The column regeneration studies were carried out using 10% NaOH as eluant for three sorption-desorption cycles. The high arsenic removal ability and regeneration efficiency of this biosorbent suggest its applicability in industrial processes and data generated would help in further upscaling of the adsorption process. © 2009 American Chemical Society.